Dramaturgi Petani Perempuan Dusun Selasih, Gianyar-Bali dalam Penolakan Penggusuran Lahan Pisang melalui Aksi Telanjang Tahun 2019 - Muliantari, Ni Putu Putri; Bandiyah, Bandiyah; Apriani, Kadek Dwita (Jurnal Nawala Politika, 2021)
ABSTRACT This study aims to determine the role of dramaturgy by peasant woman in Selasih, Gianyar-Bali in the topless movement that occurred in 2019. The theory of Dramaturgy by Erving Goffman is used for analysis to discuss the concept of front stage and back stage that occurs when this movement happens. Used a qualitative method through observation, interviews and documentation where the author lives in and participates in several daily activities to obtain a deeper analysis. The results of this study are: first, the author found a dramaturgy of topless movements carried out by peasant women in Selasih. Second, peasant women have a role to make the audience feel sorry and stop the evictions that have been prepared by male members of the farmers' union. Third, behind the actors and reality, there are facts that women have other interests outside of planning, that is to protect ecology by rejecting capitalism-patriachal. Keywords: Dramaturgy, Peasant Woman, Topless Movement, Capitalism-Patriachal.